The molecular mechanisms of ferroptosis and its role in glioma progression and treatment - Lu, Mengyang; Zhou, Yuanshuai; Sun, Linjuan; Shafi, Shaheryar; Ahmad, Nafees; Sun, Minxuan; Dong, Jun (Frontiers in Oncology, 2022)
Ferroptosis is one of the programmed modes of cell death that has attracted widespread attention recently and is capable of influencing the developmental course and prognosis of many tumors. Glioma is one of the most common primary tumors of the central nervous system, but effective treatment options are very limited. Ferroptosis plays a critical role in the glioma progression, affecting tumor cell proliferation, angiogenesis, tumor necrosis, and shaping the immune-resistant tumor microenvironment. Inducing ferroptosis has emerged as an attractive strategy for glioma. In this paper, we review ferroptosis-related researches on glioma progression and treatment.